Basin‐scale circulation and heat fluxes in ice‐covered lakes. (12th February 2014) - Rizk, William; Kirillin, Georgiy; Leppäranta, Matti
Abstract : A field and theoretical study of the mean circulation patterns, gravity currents, and heat fluxes in a mid‐latitude, ice‐covered lake is presented. Thermistor chains captured the lake‐wide pressure gradients and thermal regime, acoustic instruments measured bottom and interior velocities, and a sediment temperature probe measured sediment temperatures and heat fluxes. Typical Rossby numbers showed that the mean circulation was geostrophic, in the form of either an anti‐cyclonic or a cyclonic basin‐scale gyre. Each gyre reached a steady state after ∼ 10–15 d, circulating at a maximum velocity of ∼ 1 mm s −1 . The gyres persisted throughout most of the winter and generally decayed with time. The cyclonic gyre was generated by the lateral temperature gradients created by sediment heat release. It was not possible to determine the driver of the anti‐cyclonic gyre. Because most ice‐covered lakes are controlled by the Earth's rotation, anti‐cyclonic and cyclonic circulation is postulated as being the most common mean interior flow pattern. The horizontal heat fluxes were of the same order as the vertical heat fluxes, which is consistent with the findings of previous research. The sediment heat flux decayed with time, stabilizing after ∼ 60 d. A scaling analysis of down‐sloping advection with dynamic, seasonal‐scale temperatures showed that a warmer lake and an increase in the length‐to‐depth geometric aspect ratio (both within a given lake) and an increase in lake size all increased advection time scales, and therefore circulation time scales, near the boundaries.